2020
DOI: 10.3390/antibiotics9040166
|View full text |Cite
|
Sign up to set email alerts
|

Taurolidine Acts on Bacterial Virulence Factors and Does Not Induce Resistance in Periodontitis-Associated Bacteria—An In-Vitro Study

Abstract: The aims of the present study were: (a) to determine the mechanism of action of taurolidine against bacterial species associated with periodontal disease, and (b) to evaluate the potential development of resistance against taurolidine as compared with minocycline. After visualizing the mode of action of taurolidine by transmission electron micrographs, the interaction with most important virulence factors (lipopolysaccharide (LPS), Porphyromonas gingivalis gingipains, Aggregatibacter actinomycetemcomitans leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…16,42 Following 50 passages with subinhibitory concentrations of taurolidine, the MIC of Porphyromonas gingivalis increased 4-fold. 43 However, this increase in MIC was reversed by removal of taurolidine and only represented the upper range of wild-type MICs for most bacteria. A separate study investigating development of resistance showed no resistant subpopulations or mutants using large inocula (.10 9 bacteria/ mL) for 2 strains each of E. coli, P. aeruginosa, S. aureus, E. faecalis, and E. faecium at concentrations of 2-4X MIC.…”
Section: Pharmacodynamics With Planktonic Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…16,42 Following 50 passages with subinhibitory concentrations of taurolidine, the MIC of Porphyromonas gingivalis increased 4-fold. 43 However, this increase in MIC was reversed by removal of taurolidine and only represented the upper range of wild-type MICs for most bacteria. A separate study investigating development of resistance showed no resistant subpopulations or mutants using large inocula (.10 9 bacteria/ mL) for 2 strains each of E. coli, P. aeruginosa, S. aureus, E. faecalis, and E. faecium at concentrations of 2-4X MIC.…”
Section: Pharmacodynamics With Planktonic Cellsmentioning
confidence: 97%
“…51 Furthermore, taurolidine is able to mitigate the cytokine production of white blood cells in response E. coli-derived lipopolysaccharides, S. aureus-derived toxic shock syndrome toxin-1, and heat-killed C. albicans in a dose-dependent manner. 43,52,53 The mechanism of decreasing bacterial adhesion to epithelial cells and cytokine production of white blood cells both appear to be due to taurolidine acting upon the human cells rather than bacterial constituents. Finally, taurolidine is also reported to have antineoplastic effects ranging from anti-inflammatory property, stimulation of apoptosis, inhibiting angiogenesis, and preventing tumor adhesion, among others.…”
Section: Neutralizing Virulence and Immunoregulationmentioning
confidence: 99%
“…Taurolidine solutions are used during lung transplantations [20]. Taurolidine was researched for adjunct use during dental implantation, with a focus on how it affects the buccal microbiome [21,22]. It has shown good results when used during spinal fusion surgery [23].…”
Section: Clinical Evaluation Planmentioning
confidence: 99%